2009
DOI: 10.1177/1750698008102055
|View full text |Cite
|
Sign up to set email alerts
|

Fixing the floating gap: The online encyclopaedia Wikipedia as a global memory place

Abstract: The article proposes to interpret the web-based encyclopaedia Wikipedia as a global memory place. After presenting the core elements and basic characteristics of wikis and Wikipedia respectively, the article discusses four related issues of social memory studies: collective memory, communicative and cultural memory, `memory places' and the `floating gap'. In a third step, these theoretical premises are connected to the understanding of discourse as social cognition. Fourth, comparison is made between the poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
105
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(107 citation statements)
references
References 34 publications
0
105
0
2
Order By: Relevance
“…The Internet provides a large amount of data which researchers can collect unobtrusively and almost in real time, and the massive backup into digital archives allows scholars to conduct longitudinal studies on these data, without giving up the spontaneity of interactions [17,13]. In this context, Wikipedia, where users share their thoughts and perspectives to reach a common view on events, seems particularly appropriated for the study of traumatic events [16,26,40].…”
Section: Automated Natural Language Processing Of Events In Wikipediamentioning
confidence: 99%
See 1 more Smart Citation
“…The Internet provides a large amount of data which researchers can collect unobtrusively and almost in real time, and the massive backup into digital archives allows scholars to conduct longitudinal studies on these data, without giving up the spontaneity of interactions [17,13]. In this context, Wikipedia, where users share their thoughts and perspectives to reach a common view on events, seems particularly appropriated for the study of traumatic events [16,26,40].…”
Section: Automated Natural Language Processing Of Events In Wikipediamentioning
confidence: 99%
“…In particular, we intend collective memory as the continuous active process of sensemaking and negotiation between past and present [31] and we interpret Wikipedia as a collective memory place [40], where the discursive formation of memories takes place.…”
Section: Introductionmentioning
confidence: 99%
“…The "connectivity turn" is redefining the whole meaning of memory "mediatization" (Hoskins, 2011). It has been claimed that new media are changing the way in which different actors mediate different historical narratives to the wider society in order to achieve sociopolitical goals in the present (Hoskins, 2001(Hoskins, , 2011Huyssen, 2000;Pentzold, 2009;Pogačar, 2009;Reading, 2009Reading, , 2011aReading, , 2011bVan-House & Churchill, 2008).…”
Section: Collective Memory and Mediamentioning
confidence: 98%
“…Prior research has demonstrated that digital media can mediate collective memory processes as well as create a new form of memory production [7,8]. For example, Pentzold [9] has argued that Wikipedia is a global memory place where participants can provide and debate divergent interpretations of the past, resulting in "the formation and ratifications of shared knowledge that constitutes collective memory" [9]. This platform is global because it is open to anyone who has access to the Internet and is thus not constrained by national boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…For example, editors of the Chinese version of Wikipedia can be any online user who understands the Chinese language. The site is conceived as a memory place in the sense that it enables contributors from heterogeneous backgrounds to participate in "an intense process of discursive knowledge constitution" [9].…”
Section: Introductionmentioning
confidence: 99%